The T Cell Response to the Contact Sensitizer Paraphenylenediamine Is Characterized by a Polyclonal Diverse Repertoire of Antigen-Specific Receptors - Oakes, Theres; Popple, Amy Lee; Williams, Jason; Best, Katharine; Heather, James M.; Ismail, Mazlina; Maxwell, Gavin; Gellatly, Nichola; Dearman, Rebecca J.; Kimber, Ian; Chain, Benny (Frontiers in Immunology, 2017)
Paraphenylenediamine (PPD) is a common component of hair dyes and black henna tattoos, and can cause skin sensitisation and allergic contact dermatitis (ACD). The cutaneous inflammatory reaction associated with ACD is driven by both CD4+ and CD8+ T cells. However, the characteristics of such responses with respect to clonal breadth and magnitude are poorly defined. In this study, we have characterised the in vitro recall response of peripheral blood T cells prepared from PPD allergic individuals to a PPD-human serum albumin (HSA) conjugate (PPD-HSA). Quantitative high throughput sequencing was used to characterise the changes in the repertoire of T cell receptor (TCR) α and β genes after exposure to antigen in vitro. The PPD conjugate induced expansion of T cells carrying selected TCRs, with around 800 sequences (around 1%) being 8 or more times as abundant after culture than before. The expanded sequences showed strong skewing of V and J usage, consistent with an antigen driven clonal expansion. The Complementarity Determining Region (CDR) 3 sequences of the expanded TCRs could be grouped into several families of related amino acid sequence, but the overall diversity of the expanded sample was not much less than that of a random sample of the same size. The results suggest a model in which PPD-HSA conjugate stimulates a broad diversity of TCRs, with a wide range of stimulation strengths, which manifest as different degrees of in vitro expansion.